Nursing Home Design with a Biophilic Architectural Approach - Oya Meditya Br Sembiring; Yulesta Putra (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Older people sometimes become a new problem for a family or government. These problems are the unavailability of access to health care, the lack of old age insurance, and the social support from the family to care for them. The aging process certainly has an impact on all aspects of life, especially health because with increasing age, the function of the body's organs will decrease both due to scientific factors or disease. The decreased function of the body's organs makes the elderly limited in carrying out activities because of the limited energy they have. Through the design of the Nursing Home with the Biophilic Architecture approach, it can help the elderly from feeling lonely and so that their illness does not get worse and it is hoped that they can recover and continue to carry out more productive activities. So this design can be a social space for the elderly who are able to respond to the conditions and activities of the elderly.